2004
DOI: 10.1029/2004gb002270
|View full text |Cite
|
Sign up to set email alerts
|

Does within‐bog spatial variability of mercury and lead constrain reconstructions of absolute deposition rates from single peat records? The example of Store Mosse, Sweden

Abstract: [1] Recent research has recognized the utility of the peat record in ombrotrophic bogs to reconstruct past changes in the atmospheric deposition of, for example, lead and mercury. Frequently, these reconstructions rely only on single peat records to make assessments of regional deposition rates. The surface of a bog is not a uniform feature; rather, vegetation and micro-topography vary over small spatial scales, which can affect the interception and retention of atmospheric deposition, and over relatively shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 50 publications
(105 reference statements)
13
75
2
1
Order By: Relevance
“…PAAS normalised peat samples (one sample per metre) match Group I (light grey) and Atherton basalt (dark grey) patterns rather than those of Group II (hatched) source rocks (C). Bindler et al (2004) suggested significant with-in bog variations in elemental concentrations (but not lead isotopes) occur and recommend multi-core studies for accurate reconstruction of atmospheric deposition at a site. In addition to the long core discussed here, Ca, Al, Mg and ash content were determined in a short core (6 m) taken from Lynch's Crater in July 2003 .…”
Section: Pb Concentrations and Isotopesmentioning
confidence: 97%
See 1 more Smart Citation
“…PAAS normalised peat samples (one sample per metre) match Group I (light grey) and Atherton basalt (dark grey) patterns rather than those of Group II (hatched) source rocks (C). Bindler et al (2004) suggested significant with-in bog variations in elemental concentrations (but not lead isotopes) occur and recommend multi-core studies for accurate reconstruction of atmospheric deposition at a site. In addition to the long core discussed here, Ca, Al, Mg and ash content were determined in a short core (6 m) taken from Lynch's Crater in July 2003 .…”
Section: Pb Concentrations and Isotopesmentioning
confidence: 97%
“…Lead isotopes have been applied previously to trace deposited dusts (Rosman et al, 1997;Shotyk et al, 2001;Kylander et al, 2005) and Pb is known to be immobile in peat (Bindler et al, 2004;Shotyk et al, 2005 and references therein). Both Pb and REE are largely incorporated into accessory phases and subject to release under similar weathering conditions (Harlavan and Erel, 2002).…”
Section: Pb Isotopesmentioning
confidence: 97%
“…The surface peat core was wrapped in plastic and transported back to the laboratory where it was frozen, the outer surface was hand planed and the clean monolith cut into horizontal slices (1-to 5-cm thick). The peat core was dated using wiggle matching (Bindler et al, 2004), i.e. by comparing the lead concentration and the 206 Pb/ 207 Pb ratio trends in the peat (see electronic annex file) with the same trends in the sediment of Lake Grånästjärnen, 40 km from the smelter and 40 km from Vorrmyran ( Fig.…”
Section: Soil Samplingmentioning
confidence: 99%
“…Many upland peat soils, downwind of urban and industrial centres, are contaminated with anthropogenically derived, atmospherically deposited metal ions, such as Pb, Cu and Hg (c.f. Livett et al 1979;Benoit et al 1998;Martinez Cortizas et al 1999;Weiss et al 1999;Vile et al 2000;Shotyk et al 2000;Bindler et al 2004;Farmer et al 2005). This is due to the strong affinity of peat for these metal ions and the accumulating nature of this organic-rich soil.…”
Section: Introductionmentioning
confidence: 95%